Economic Contribution of Street Vendors to the Urban Society in Nepal - Thapa, Bhim K.; Pant, Sushil K.; Paudel , Ramesh R. (Molung Educational Frontier, 2026)
This study explores the economic contributions of street vendors to society, focusing on their roles in self-employment, employment generation for others, and the provision of affordable goods and services, as well as the challenges they face in sustaining their businesses. It aims to highlight the significance of street vending in urban economies and the need for supportive policies. The research employed qualitative methods to collect data from nine street vendors through semi-structured interviews. All street vendors within Ratna Park and Sundhara in Kathmandu were included in the population, and purposive sampling was used to select the interview sample. The research demonstrates that street vending supports livelihoods by generating self-sustaining income, jobs for families and acquaintances, and affordable goods for communities. However, its sustainability is threatened by strict regulations, limited operating hours, and harassment from authorities. The streets of urban areas generate employment through vending that assists low-income families and enables their financial independence. The system’s stability is constrained by regulatory challenges. This research demonstrates that vendors require both government recognition of their economic contributions and formal regulatory systems to safeguard their sustainability. This research contributes new empirical knowledge on the functions of the formal economy and the monitoring difficulties that affect street vendors in Kathmandu. The research proves the need for government policies that merge urban governance activities with the development of informal entrepreneurial opportunities.